2020
DOI: 10.1099/ijsem.0.004164
|View full text |Cite
|
Sign up to set email alerts
|

Francisella salimarina sp. nov., isolated from coastal seawater

Abstract: Four strains (SYSU SYW-1T, SYW-2, SYW-3 and XLW-1) were isolated from seawater near the shore in Guangdong Province, China. Cells were Gram-stain-negative, aerobic, non-motile and non-spore-forming. Growth was observed at a temperature range of 16–40 °C (optimum, 32 °C), a pH range of 4–8 (optimum, pH 7) and in the presence of up to 10 % (w/v) NaCl. The major polar lipids were diphosphatidylglycerol, phosphatidylcholine, phosphatidylethanolamine and an unidentified phospholipid. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 54 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…The scheme provided in Table 4 can be used for the identification of Francisellaceae. According to our data and the literature [13][14][15][16][17][18][19], the 5182-5185 mass of the 50S ribosomal protein L34 was specific for the Francisella genus. Within the Francisella genus, the species F. tularensis could be differentiated from the other Francisella species by the histone-like protein form Beta (Hu-beta) mass (selected biomarker 9449).…”
Section: Francisella Identification By Biomarkersupporting
confidence: 71%
See 2 more Smart Citations
“…The scheme provided in Table 4 can be used for the identification of Francisellaceae. According to our data and the literature [13][14][15][16][17][18][19], the 5182-5185 mass of the 50S ribosomal protein L34 was specific for the Francisella genus. Within the Francisella genus, the species F. tularensis could be differentiated from the other Francisella species by the histone-like protein form Beta (Hu-beta) mass (selected biomarker 9449).…”
Section: Francisella Identification By Biomarkersupporting
confidence: 71%
“…Manual adjustments were made when necessary. F. salinarina [19], F. oppertunistica [31], A. frigiaqua, A. inopinata [32], and Pseudofrancisella aestuarii [33] are genetically related to F. tularensis. Except for F. oppertunistica, the species were found in cold (sea)water without any relation to human pathogenicity.…”
Section: Calculation Of Biomarker Masses From Dna Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial proportion of these "other" bacteria (5.0% and 12.0% in the ONT 16S and ONT Custom, respectively) belonged to Francisella species, which could not be classified to species level with SILVA taxonomy. Further classification of sequences matching to this taxon was performed with EMBL-EBI/ ENA taxonomy, which revealed that over 99.9% of these sequences matched best to F. salina (synonym F. marina, now F. salimarina; Li et al 2020), indicating this was due to the absence of this species in the SILVA taxonomy. Taking this into account, the average relative abundance of bacteria that should not be present in the mock community was reduced to 5.8% for both ONT protocols.…”
Section: Mock Community Analysismentioning
confidence: 99%